Anne of Green Gables - Chan, Crystal S. (Manga Classics, Inc., 2020)
Graphic novel adaptation of the novel "Anne of Green Gables," in which siblings Marilla and Matthew Cuthbert adopt a plucky orphan named Anne whose antics and adventures cause an uproar on Prince Edward Island and endear her to the hearts of everyone she meets.